2015
DOI: 10.1186/s40101-015-0078-y
|View full text |Cite
|
Sign up to set email alerts
|

Decline in objective physical activity over a 10-year period in a Japanese elementary school

Abstract: BackgroundThe purpose of this study was to examine the change in accelerometer-derived daily physical activity (PA) and activity record-derived daily activities over a 10-year period in urban elementary schoolchildren in Japan.MethodsA total of 233 sixth-grade children (11–12 years old) in a same elementary school in Kyoto participated in the study (n = 125 and 108 in 1999 and 2009, respectively). The participant rate is 91.9 and 98.2 % in 1999 and 2009, respectively. The size and shape of the school district … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Despite the lack of a significant difference in PAL between boys and girls in the present study, boys took significantly around 2,500 more steps/d than girls (12,578 vs. 10,031). The difference was also similar with the results from most studies reporting elementary school boys having higher step counts than elementary school girls in other countries 6 , 11 , 28 , 29 . In the United states, urban elementary school boys took significantly around 4,000 more steps/d than girls (16,421 vs. 12,332) 28 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Despite the lack of a significant difference in PAL between boys and girls in the present study, boys took significantly around 2,500 more steps/d than girls (12,578 vs. 10,031). The difference was also similar with the results from most studies reporting elementary school boys having higher step counts than elementary school girls in other countries 6 , 11 , 28 , 29 . In the United states, urban elementary school boys took significantly around 4,000 more steps/d than girls (16,421 vs. 12,332) 28 .…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, in Japan, Itoi et al . 11 reported that urban elementary school boys took significantly around 1,500 more steps/d than girls (12,237 vs. 10,748). On the other hand, in Korea, a similar population of elementary school boys had similar steps as girls (11,165 vs. 10,708) 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A negative trend in most aspects of physical fitness, as observed in school‐aged children over a 20‐year interval, is a worrying health trend all over the world and will compromise well‐being of future adults . Modern children have lower physical activity than the children of a decade ago as a result of less time being spent playing outdoors or active transport to school . PAL in school‐aged children, as measured with accelerometers, are shown to decrease in many countries .…”
Section: Discussionmentioning
confidence: 99%